A Study of Trichomonas vaginalis Infection and Correlates in Women with Vaginal Discharge Referred at Fann Teaching Hospital in Senegal. (1st April 2019) - Tine, Roger C.; Sylla, Khadime; Ka, Rougyatou; Dia, Lamine; Sow, Doudou; Lelo, Souleye; Diallo, Khardiata; Faye, Babacar; Dieng, Thérèse; Ndour, Cheikh T.; Sow, Ahmet Y.
Abstract : Introduction . Trichomoniasis is nowadays the most prevalent non-viral sexually transmitted infection in the world. In Senegal, the epidemiology of trichomoniasis is not well known. The current study aimed at assessing the prevalence and factors associated with T. vaginalis infection among women with vaginal discharge. Methods . A retrospective analysis of laboratory records from patients referred at the Fann Teaching Hospital in Dakar, Senegal, for vaginal discharge was carried out. The study covered the period from 2006 to 2011. For each participating woman, a vaginal swab was collected and a wet mount smear performed immediately. Optic microscopic examination with 40x magnification was done to detect T. vaginalis and assess biological modifications such as presence of epithelial cells, white blood cells, and red blood cells. A gram stained smear was also performed and examined under oil immersion (100x magnification) to assess the vaginal flora. Results . Overall, 3893 women were enrolled with a mean age at 31.2 ± 10 years. The prevalence of Trichomoniasis represented 4.8%, 95%CI(3.1-5.7) and it was lower among women less than 30 years (4.1%), while divorced women more likely to be infected compared to married and single women (aOR:2.1, 95%CI (1.2-3.7)). Trichomoniasis was associated with abnormal vaginal flora such as type III (aOR:2.6, 95%CI(1.5-4.4)) and type IV (aOR:3.3, 95%CI(2.1-5.3)). In addition, patients with erythrocytes excretion were more likely to be infected by T. vaginalis (aOR:2.8, 95%CI(1.9-3.9). Conclusion . Trichomonas vaginalis remains prevalent among sexually active women. Strategies aiming at improving disease awareness in these high-risk groups are needed to improve trichomoniasis prevention but extensive epidemiological data are still needed for a better understanding of the disease transmission dynamic.